Contributing factors of teenage fatherhood in South Africa - Koketso, Matlakala Frans (Penerbit Universiti Kebangsaan Malaysia, 2020)
Teenage fatherhood is a serious problem globally and South Africa is not an exception. The challenge with teenage fatherhood is that it is under-represented and wrongly portrayed in media. It is mainly assumed that teenage fathers tend to deny their children at birth and that they are difficult to locate and study. This study was intended at exploring contributing factors of teenage fatherhood in South Africa. The author reviewed and analysed literature as a research design. The study adopted Psychosocial theory because of its ability to explain human development. This theory was ideal to explain the influence of environment in relation to teenage fatherhood. The literature showcases that teenagers engage in reckless sexual activities and disregard the use of contraceptives which is linked to conduct disorder. Moreover, teenagers engage in sexual intercourse in order to make an impression to their peers to prove that they are man enough. However, they are challenged by financial dependency and the role that comes with caring for their children. In conclusion, this paper demonstrated that teenage fathers are not studied by scholars because they are seen as a minority group. Be as it may, teenage fathers should not be confused with teenage mothers and researchers need to also acknowledge the environment when assessing the contributing factors of teenage fatherhood. Thus, this study recommends that teenage fathers should receive equal attention from scholars as their counterparts – teenage mothers.